How to make a home - Hollis, Edward, ....- (London : Macmillan, 2016)
At a time when work and home life are becoming increasingly blurred, and modern technology brings the realm of the public into what used to be a personal and private space, Ed Hollis looks at what it means to make a home in today's world. Exploring the meaning of private and public space, the importance we place on physical objects and the demands we make of our home environment, How to Make a Home challenges us to re-imagine the concept of home and hearth.
Keywords: Wonen